Nasal Gout: A Rare Pathology - Conceição Peixoto, Maria (ENT Updates, 2022)
Gout is the most frequent cause of inflammatory arthritis. However, it may present atypical deposit sites for monosodium urate crystals, making its diagnosis difficult, particularly if there is no previous history of hyperuricemia. The aim of this study is to present a rare form of presentation of a common pathology such as gout with tophaceous gout involving the nasal dorsum as the first presentation. We report a 47-yearold male who presented at our clinic due to nasal deformity with progressive growth and a painful lesion located in the right nasal ridge. Due to the absence of other complaints or associated pathologies, and regarding CT evaluation which confirm a lesion on the right side of the nasal pyramid, with apparently well-defined limits, with an anteroposterior axis of approximately 10 mm, no diagnosis was possible without histologic findings. The patient underwent surgery to excise the lesion and the histological evaluation of the surgical specimen revealed a gouty tuft. Due to the aesthetic deformity, grafting was performed with cartilage and temporal fascia. An analytical evaluation confirmed hyperuricemia at the same time that another gouty lesion appeared on the left hand. He was referred to a rheumatology consultation and started medication with allopurinol. Thus this case draws our attention to the fact that common pathologies can have very atypical presentations.